Youssef syndrome- manifesting as cyclical hematuria during non-pregnant state and as antepartum hemorrhage during pregnant state - Mahale, Arun Ramakrishnarao; Baravkar, Pankaj Narayan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A woman developed an utero-vesical fistula following her second cesarean section. Between pregnancies she manifested cyclical menouria without urinary incontinence. In her third pregnancy for first 3 months her cyclical menouria was relieved as a feature of pregnancy amenorrhea, but it recurred in fourth month of pregnancy as antepartum hemorrhage because of placental location in the fistula area.